Systematic Literature Review on the Effectiveness of Communicative Language Teaching (CLT) in Enhancing EFL Students’ Speaking Skills (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This research investigates the effectiveness of Communicative Language Teaching (CLT) in enhancing English language proficiency among second language learners. Using a qualitative approach, the study explores learner engagement, cultural awareness, and the role of teachers in CLT. Participants held positive perceptions of CLT, which facilitated real-life language practice and boosted their confidence. Improved English proficiency, especially in speaking, listening, and interactive skills, resulted from the learner-centred and practical nature of CLT. The research emphasizes the importance of integrating CLT techniques into language teaching and underscores the need for welldesigned teacher training programs to optimize CLT's benefits in diverse language learning contexts. This study aims to inform educators and policymakers in developing efficient and learner-centred language programs to meet the demand for English proficiency in an interconnected world.